NDM-1-producing Enterobacteriaceae in a teaching hospital in Shanghai, China: IncX3-type plasmids may contribute to the dissemination of blaNDM-1. (May 2015) - Qu, Hongping; Wang, Xiaoli; Ni, Yuxing; Liu, Jialin; Tan, Ruoming; Huang, Jie; Li, Lei; Sun, Jingyong
Highlights: This is the first report of NDM-1-positive Enterobacteriacea e from Shanghai, China. We provide the genetic characteristics of blaNDM-1 in Shanghai, China. IncX3 plasmids, reported in various species in the United Arab Emirates and China, may contribute to the dissemination of blaNDM-1. More attention should be devoted to control the dissemination of the NDM-1 gene due to its potential horizontal transfer via mobile genetic elements. Summary: Objectives: To provide the epidemiological dissemination and the genetic characteristics of blaNDM-1 in a teaching hospital in Shanghai, China. Methods: Here, the carbapenemase genes of 114 CRE isolates were evaluated by polymerase chain reaction (PCR). Clonal relatedness was assessed by pulsed-field gel electrophoresis (PFGE). Conjugation experiments and Southern blot hybridization were performed to determine the transferability of plasmids. Then plasmids were completely sequenced by the shotgun method. Results: Two Klebsiella pneumoniae strains (RJA1227 and RJF866) and one Raoultella planticola strain (RJA274) were identified as NDM-1 positive. The two K. pneumoniae isolates belonged to ST11 and exhibited highly similar PFGE patterns. Shotgun sequencing showed that plasmid pRJF866 (ca. 110 kb) contained genes associated with the IncFII-FIB group and was highly similar to plasmid pKOX_NDM1. RJA274 (ca. 50 kb) harbored bla NDM-1 on an IncX3 plasmid, which was nearly identical to plasmid pNDM-HN380 except that part of the IS Aba125 element is missing. Conclusion: This is the first report of NDM-1-positive Enterobacteriacea e from Shanghai, China. IncX3 plasmids, reported in various species in the United Arab Emirates and China, may contribute to the dissemination of blaNDM-1. . More attention should be devoted to monitoring the dissemination of the NDM-1 gene due to its potential horizontal transfer via mobile genetic elements.